A Call for Amicus Briefs as a Means to Influence Special Education Policy: Lessons Learned From Endrew F. (December 2019) - Lewis, Maria M.; Bray, Laura E.
Given the legal nature of special education, a particularly promising avenue for infusing research into practice is through court cases. Recent work has illuminated the influence of amicus briefs in court decisions. An amicus brief is a nonparty brief submitted by a person, group of people, or organization that provides insight and expertise on issues presented in a case. In this exploratory study, we examined how interest groups, through the amicus brief process, used research in a recent Supreme Court case, Endrew F. v. Douglas County School District . The case focused on a fundamental principle at the heart of the Individuals with Disabilities Education Act, the definition of a free appropriate public education, an issue in which researchers, practitioners, and policymakers alike should be interested. Our findings indicate that researchers and research played a limited role in the briefing process. We conclude with a discussion of potential reasons for the lack of research in the briefing process, as well as a call for the field to use amicus briefs as a means to influence special education policy and practice.